Kajian Daya Dukung Daerah Aliran Sungai (DAS) Anai Provinsi Sumatera Barat - Aisyah Amini; Eri Barlian; Nurhasan Syah; Iswandi Umar; Dewi Rahmadani Siregar (Postgraduate, University of Mataram, 2025)
This study aims to assess the carrying capacity of the Anai River Basin (Watershed) in West Sumatra Province in response to increasing anthropogenic pressures and environmental changes. The research employed a spatial analysis approach utilizing remote sensing data and geographic information systems (GIS) to evaluate land cover conditions, water quality, and erosion levels. Carrying capacity analysis was conducted by calculating an environmental carrying capacity index, which included hydrological aspects, water quality, and the ecosystem's capacity to provide environmental services. The results indicate that the Anai River Basin is experiencing significant ecological pressure from land use changes, particularly the conversion of forests into agricultural land and settlements. Erosion rates in several sub-watersheds reached moderate to severe categories, with an average value of 15-25 tons/ha/year. River water quality demonstrated a decline in several parameters, especially increased turbidity levels and sediment content during the rainy season. The hydrological carrying capacity of the Anai watershed remains in a moderate category (index 0.65) but has shown a declining trend over the last five years. The findings indicate the necessity for implementing sustainable watershed management strategies. Management recommendations include forest conservation in upstream areas, the application of soil and water conservation techniques on agricultural land, the development of a regular water quality monitoring system, area zoning based on vulnerability levels, rehabilitation of 2,500 hectares of critical land, and the strengthening of watershed management institutions involving the active participation of local communities.